Sturge-Weber syndrome: A case report - Mukhopadhyay S (Wolters Kluwer Medknow Publications, 2008)
A 6½ year-old female child has been described. The condition is characterized by port wine stains in the body, massive gingival overgrowth, history of convulsive disorder, and dilated ocular vessels.